Thrombotic vascular risk factors in inflammatory bowel disease. Issue 5 (May 1996) - Hudson, M; Chitolie, A; Hutton, R A; Smith, M S; Pounder, R E; Wakefield, A J
Abstract : BACKGROUND--Thrombosis may be an important effector mechanism in the pathogenesis of Crohn's disease. METHODS--This study therefore investigated the prevalence of independent thrombotic risk factors (factor VII coagulant activity, lipoprotein (a), fibrinogen, plasma triglycerides, and smoking) in patients with Crohn's disease, ulcerative colitis, and normal controls. RESULTS--In Crohn's disease (n = 75), the mean plasma VII:C, lipoprotein (a) and fibrinogen concentrations were significantly greater than in the normal population (n = 85). In ulcerative colitis (n = 35), only the mean factor VII:C concentration was significantly higher than normal. Ninety three per cent of patients with Crohn's disease and 86% of those with ulcerative colitis had at least one risk factor for thrombotic vascular disease, compared with 61% of the normal population (p < 0.001). CONCLUSIONS--In many young patients with inflammatory bowel disease, plasma concentrations of these prothrombotic factors were in excess of the limits that are regarded as posing an increased risk for the development of occlusive vascular disease.